229k views
5 votes
6(2x-3)-8=-2
Solve for x! Tyy

User Sacheen
by
5.0k points

2 Answers

3 votes

6(2x -3) - 8 = -2 (remove the parantheses)

12x - 18 - 8 = -2 (calculate)

12x - 26 = -2 (move the constant to the right)

12x = -2 + 26 (calculate)

12x = 24 (divide both sides)

x = 2

User Shushan
by
5.2k points
4 votes

Answer:

x=2

Explanation:

use distributive property for the first part the solve like usual

hope this helped

6(2x-3)-8=-2 Solve for x! Tyy-example-1
User Israelm
by
4.7k points